SOCIOCULTURAL PERSPECTIVES ON THE DEVELOPMENT OF MEGATECHNOLOGIES IN THE KNOWLEDGE SOCIETY - Chenbaі, Nataliia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
At the beginning of the new millennium, most models of social development proposed in the 1960s–1980s came under critical reconsideration. This shift is associated with the growing awareness of uncertainty and risks in contemporary society and the limitations of classical rationality in explaining complex transformations.The phenomenon of megatechnologies has become an object of interdisciplinary research. However, despite numerous studies, the problem of the sociocultural consequences of megatechnologies, particularly in relation to the crisis of rationality in the knowledge society, remains insufficiently explored, which determines the relevance of this study. The aim and tasks. The aim is to identify, on the basis of socio-philosophical analysis, the sociocultural prospects of megatechnologies in the knowledge society and to clarify their role in the emergence and deepening of the crisis of rationality in contemporary society. Research methods. The study employs sociocultural and axiological methodological approaches, the principle of complementarity, as well as the methods of logical analysis and synthesis to examine the interrelation between the development of megatechnologies and the transformation of rationality. Research results. It has been established that the spread of megatechnologies is accompanied not only by the expansion of human capabilities but also by the intensification of risks associated with changes in values, communication, and social interaction. The analysis shows a shift from fundamental to instrumentally oriented knowledge, which leads to the narrowing of rationality to pragmatic functions. This transformation can be interpreted as a crisis of rationality, which becomes a defining feature of the knowledge society. Discussion. The dynamics of the knowledge society reveal a contradiction between technological growth and sociocultural development, expressed in the inability of existing rational frameworks to interpret these transformations. The expansion of megatechnologies contributes to new forms of dependence, manipulation, and fragmentation of experience, which deepens the crisis of rationality. Conclusions. The study demonstrates that megatechnologies act not only as instruments of technological progress and as factors in forming a new sociocultural reality characterized by a systemic crisis of rationality. In this context, the assessment of technological prospects requires a reconsideration of value priorities and the development of interdisciplinary approaches aimed at overcoming or mitigating this crisis.